2013
DOI: 10.1371/journal.pone.0078111
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunomodulatory Effects of Three Probiotic Strains Isolated from the Feces of Breast-Fed Infants in Healthy Adults: SETOPROB Study

Abstract: We previously described the isolation and characterization of three probiotic strains from the feces of exclusively breast-fed newborn infants: Lactobacillus paracasei CNCM I-4034, Bifidobacterium breve CNCM I-4035 and Lactobacillus rhamnosus CNCM I-4036. These strains were shown to adhere to intestinal mucus in vitro, to be sensitive to antibiotics and to resist biliary salts and low pH. In the present study, a multicenter, randomized, double-blind, placebo-controlled trial with 100 healthy volunteers in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 29 publications
4
36
0
1
Order By: Relevance
“…It has been demonstrated that probiotics can affect the structure of gut microbiota and the interaction with the microbial community and the host health through different mechanisms [12,[193][194][195]. These effects are mediated by the direct or indirect action of probiotics and can involve the modulation of the immune system or that of remote organs like the brain and liver due to the production of metabolites finally localized in these organs [193,[196][197][198][199].…”
Section: Probiotic Administration Microbiota Bile Acids and Cardiovmentioning
confidence: 99%
“…It has been demonstrated that probiotics can affect the structure of gut microbiota and the interaction with the microbial community and the host health through different mechanisms [12,[193][194][195]. These effects are mediated by the direct or indirect action of probiotics and can involve the modulation of the immune system or that of remote organs like the brain and liver due to the production of metabolites finally localized in these organs [193,[196][197][198][199].…”
Section: Probiotic Administration Microbiota Bile Acids and Cardiovmentioning
confidence: 99%
“…Oral administration of these LAB strains modified the bacterial populations in the feces of the volunteers, and all three strains exerted varying degrees of immunomodulatory effects [20]. Thus, administration of B. breve CNCM I-4035 resulted in a significant increase in fecal secretory IgA content.…”
Section: Introductionmentioning
confidence: 96%
“…Results highlighting the functional effect of some probiotics in boosting the immune system (3) have led to the attempt to study the effect of probiotics on the amelioration of immunosupression therapy side effects.…”
Section: Genome Announcementmentioning
confidence: 99%